Understanding older problem drinkers: The role of drinking to cope. (January 2017) - Gilson, Kim-Michelle; Bryant, Christina; Judd, Fiona
Abstract: Introduction and aims: Despite a common perception that older adults drink less than younger adults, drinking frequency increases with age. The aim of this study was to examine the types of coping motives associated with problem drinkers in addition to the types of specific drinking problems most commonly endorsed by older drinkers. The study also sought to investigate the role of individual drinking to cope motives in problem drinking. Method: Participants were 288 community dwelling older adults aged who consumed alcohol, and were drawn from a larger study of health and aging in rural areas of Australia. Participants completed a postal questionnaire comprising the Drinking Problems Index, Drinking Motives Questionnaire, The AUDIT-C, and the Centre for Epidemiological Studies Depression Scale. Results: Overall, 22.2% of the sample were problem drinkers, with a higher prevalence for men (30.4%) than women (15.6%). Problem drinkers were significantly more likely to consume alcohol according to several indices of risky drinking. The most common drinking problems experienced were becoming intoxicated, spending too much money on drinking, feeling confused after drinking, and skipping meals. Drinking to cope motives to relax, to manage physical symptoms and to feel more self-confident increased the odds of problem drinking. Conclusions: Problem drinking is highly prevalent in older adults. Given the potential adverse consequences of problem drinking on the health of older adults it is imperative that health professionals pay attention to drinking behaviours as part of routine practice. Highlights: Problem drinking is highly prevalent in older adults. Problem drinking measures that do not assess quantity and frequency of drinking may be more suitable for older adults. Specific drinking to cope motives were associated with problem drinking. Drinking to cope motives that have a social context are more associated with problem drinking It may be important to ask older adults about their reasons for drinking.